Latex Flow Pattterns Several of Clone with the Use of Plant Growth Regulator to Production - Try Koryati; Luthfi A. M. Siregar (Jurnal Pertanian Tropik, 2019)
Slow or fast flow of latex when tapped affects the height and low production of latex. The physiological nature of the latex flow illustrates the speed and resistance of the latex flow rate per unit time. The purpose of the study was to determine the pattern of the flow rate of latex several rubber clones with the use of growth regulators and their relation to the production of latex in the initial tapping. The study was carried out in the PTP-N I Kso PTP-N III Karang Inong plantation, East Aceh. The research was arranged based on three factors of Nested Design, namely Clone factors with five factors, IAA + Kinetin hormone factor 7 factors and Paklobutrazol factors there were 3 factors. Some research results show that the pattern of each clone is different from the rate of flow of latex. In general, the clones tested were PB 260, PB 330, and IRR 5 clones, which showed a sharp decrease in latex flow, except the PB 340 and IRR 107 were still stable. PB 340 clone has the highest latex flow rate of 3.00 ml / minute in the first 10 minutes combination of H1P0 treatment. In the 90th minute, PB 340 still flows latex in several combinations of treatments with a latex flow rate in treatment (H4P1) of about 2.55 ml / minutes with a higher latex volume of 30-70 minutes for the same treatment combination. The highest production of latex per plant was obtained from the IRR 107 (K4) clone with the administration of 500 ppm IAA + 60 ppm kinetic (H4) and the application of soil paklobutrazol (P1) (K4H4P1) of 59.99 g / p / s, followed by PB clones 340 (K3H4P1)) of 49.80 g / p / s. The lowest production of latex per plant was found in PB 330 (K2H0P0) clones of (4.98 g / p / s).